Lethal hopelessness: Understanding and responding to asylum seeker distress and mental deterioration. (21st March 2017) - Procter, Nicholas G.; Kenny, Mary Anne; Eaton, Heather; Grech, Carol
Abstract: The mental deterioration of the so called 'legacy caseload' (asylum seekers who arrived in Australia by boat between August 2012–December 2013) has become a national concern and is garnering international attention. Prolonged uncertainty is contributing to mental deterioration and despair. There have been at least 11 deaths by suicide since June 2014. Social support services have been limited and legal assistance in short supply; this is associated with lengthy delays with visa applications. Thwarted belongingness, purpose and identity, a shortage of available services, and barriers to legal support for processes attendant upon Refugee Status Determination increase the likelihood that the mental health of asylum seekers will deteriorate further, potentially developing into worsening decline, which will lead to increased self‐harm and suicide. This article summarises recent suicide deaths in Australia, positing practical assistance and support for asylum seekers living in the community. Therapeutic engagement should be trauma‐informed wherever possible, helping asylum seekers to reframe their sense of lethal hopelessness.